Comparative Analysis of Building Cost Budget Plans Using SNI and BOW Methods - Taufik Safii Abdullah; Suryo Handoyo; Erni Mulyandari (Syntax Idea)
Building budget design (RAB) is a way to calculate the costs that will be required from a building and with this cost the building can be realized as planned. In Indonesia, there are methods for planning the unit cost price of project budgets, namely BOW (Burgelijke Openbare Werken) and SNI (Regulation of The Ministry of Public Works and Housing Republic Indonesia Number 1 of 2022 concerning Guidelines for Preparing Estimated Costs of Construction Work in the Field of Public Works and Public Housing) where the SNI method is an adjustment and renewal of the BOW analysis which is an analysis of the legacy of the Dutch Government which contains a labor-intensive and conventional work system. However, the reality in the field is that the BOW method is still widely used for building construction work because the coefficient used is greater than using the SNI method so that it is possible to get a greater profit. This study aims to find out the RAB of the SNI and BOW methods and then find out the difference to be an alternative reference in planning construction costs with the SNI and BOW methods and add insight. In the calculation of the budget plan for concrete work costs for the construction of the UPN Veteran Yogyakarta Integrated Research Laboratory Building using 2 methods, the SNI method was obtained at Rp 9,659,059,280.45 while using the BOW method at Rp 14,474,237,708.85. The difference between the SNI and BOW method budget plans is Rp 4,815,178,428.39.